Implications of Antiphospholipid and Antineutrophilic Cytoplasmic Antibodies in the Context of Postinfectious Glomerulonephritis. (1st February 2017) - Leifer, Daniel; Butani, Lavjay
Abstract : While antineutrophil cytoplasmic antibody (ANCA) positivity has been documented in some patients with postinfectious glomerulonephritis (PIGN) and is associated with more severe disease, antiphospholipid antibodies (APA) are not known to be a common occurrence. We describe a child with severe acute kidney injury who was noted to have prolonged positivity of both ANCA and APA; a renal biopsy showed noncrescentic immune complex mediated glomerulonephritis with subepithelial deposits compatible with PIGN. He recovered without maintenance immunosuppressive therapy and at last follow-up had normal renal function. We discuss the cooccurrence and implications of ANCA and APA in children with PIGN.